2021
DOI: 10.3390/electricity2040028
|View full text |Cite
|
Sign up to set email alerts
|

Participative Renewable Energy Community—How Blockchain-Based Governance Enables a German Interpretation of RED II

Abstract: Distributed solar photovoltaic generation is less expensive than the retail price of electricity from the grid in most parts of Europe. Growing shares of variable generation place a focus on Renewable Energy Communities (REC) to increase the economic benefits of local energy systems. Civil society could play an influential and necessary role in the development of such communities, the expansion of renewable energy capacity and the provision of flexibility. However, current RECs models still confine tenants to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Prior studies were concerned more with the relationship between oil price volatility and the stock market. Most of these studies found that the stock market is highly related to oil price volatility [4,[15][16][17][18][19][20][21]41]. However, only few studies address the oil price volatility and VIX index, and the uncertainty of the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies were concerned more with the relationship between oil price volatility and the stock market. Most of these studies found that the stock market is highly related to oil price volatility [4,[15][16][17][18][19][20][21]41]. However, only few studies address the oil price volatility and VIX index, and the uncertainty of the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the positive oil price shock has a greater effect on the VIX index than the negative oil price shock. Although oil prices may cause investors' panic, it is worth mentioning that frontier technologies such as blockchain technology may bring new changes to the crude oil market [41][42][43][44][45]. When studying the impact of international crude oil prices on the market, we may need to examine the moderator role of frontier technologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, while applications in localized parts may exist, the scalability and viability of system-wide applications are subject to further investigations. Existing regulations may also hinder the adoption of DLT, which needs to be revised [106]. Concretely, it is to be investigated if a distributed ledger in energy trading applications would be superior to a conventional centralized ledger in terms of transaction efficiency, transparency, and security.…”
Section: Distributed Ledger Technologymentioning
confidence: 99%